Feasibility of Detonation in Porous Silicon Nanoenergetics. Issue 8 (28th May 2021) - Guerieri, Philip M.; Fuchs, Brian; Churaman, Wayne A.
Abstract: Porous silicon with sodium perchlorate oxidizer is hypothesized to be a detonable explosive, which is atypical for heterogenous fuel/oxidizer composites. The existence of detonation in energetic porous silicon remains contested and would theoretically feature several unique behaviors illustrated by this study. Calculations to predict detonation performance are performed using CHEETAH thermochemical code for silicon porosities of 45–85 % surrounding 69 %, which represents an experimentally typical case. Uniquely, e‐PS detonation is predicted to produce low gas volume. At 69 % porosity, condensed detonation products comprise 78 % of the mass (varying from 86 % to 46 % for 45–85 % porosity), and therefore a low TNT equivalent mechanical energy of 0.429 (but 1.32 when comparing total detonation energy). The calculated pressure of detonation for 69 % porosity is 1.065 GPa, only about 4 % of that of typical military explosives but over 50 times greater than compression wave amplitudes estimated for fast‐burning nanothermites, which are comparable heterogenous fuel/oxidizer composites. At porosities above 67 %, computed detonation velocities are shown to exceed estimates for the unreacted speed of sound and therefore a detonation structure consistent with classical CJ theory is proposed. Indeed, published maximum experimental propagation speeds for energetic porous silicon in this upper porosity range when pore size is optimal agree well with CHEETAH computations of detonation velocity, thereby supporting that detonation is possible. Below 66 % porosity, sound speed in unreacted material overtakes the calculated detonation velocities. Traditionally this precludes formation of a detonation wave since the shockwave would decay as energy propagates ahead acoustically into unreacted material. However, experimental agreement is still observed between 60–67 % porosity. By comparing computed detonation pressure with estimates for the strength of unreacted porous silicon, this range is proposed to be a transition zone in which a detonation‐like structure could be maintained, despite the inverted sound speed comparison, by rapid catastrophic fracture of porous silicon at the detonation front. This hypothesis implies that a sonic precompression wave must precede the detonation wave since at least a minor fraction of shock energy would propagate ahead in unreacted material. Finally, comparisons are made with baseline primary explosives and nanothermites showing that among metal‐based composite energetics on the basis of reaction rate and detonation pressure, energetic porous silicon currently exhibits the most promise for replacing primary explosives at reasonable densities in igniters and augmenting initiator formulations. Abstract :